Conserved HA-peptides expressed along with flagellin in Trichoplusia ni larvae protects chicken against intranasal H7N1 HPAIV challenge. Issue 3 (16th January 2020) - Sisteré-Oró, Marta; Martínez-Pulgarín, Susana; Solanes, David; Veljkovic, Veljko; López-Serrano, Sergi; Córdoba, Lorena; Cordón, Ivan; Escribano, José M.; Darji, Ayub
Highlights: Extracts of T . ni larvae expressing flagellin-NG34/CS17 protected chickens against a heterologous H7N1 IV strain. Flagellin-NG34/CS17 vaccinated chickens saved from flu-like clinical signs. Flagellin-NG34/CS17 vaccinated chickens limited oropharyngeal and cloacal shedding. Flagellin-NG34/CS17 induced an increase in IgM and improved IgY response. Abstract: The immunization of poultry where H5 and H7 influenza viruses (IVs) are endemic is one of the strategies to prevent unexpected zoonoses. Our group has been focused on conserved HA-epitopes as potential vaccine candidates to obtain multivalent immune responses against distinct IV subtypes. In this study, two conserved epitopes (NG-34 and CS-17) fused to flagellin were produced in a Baculovirus platform based on Trichoplusia ni larvae as living biofactories. Soluble extracts obtained from larvae expressing "flagellin-NG34/CS17 antigen" were used to immunize chickens and the efficacy of the vaccine was evaluated against a heterologous H7N1 HPAIV challenge in chickens. The flagellin-NG34/CS17 vaccine protected the vaccinated chickens and blocked viral shedding orally and cloacally. Furthermore, no apparent clinical signs were monitored in 10/12 vaccinated individuals. The mechanism of protection conferred is under investigation.